Subcellular Targeting of VIP Boutons in Mouse Barrel Cortex is Layer-Dependent and not Restricted to Interneurons. (28th August 2017) - Zhou, Xiaojuan; Rickmann, Michael; Hafner, Georg; Staiger, Jochen F
Abstract: Neocortical vasoactive intestinal polypeptide (VIP) expressing cells are a diverse subpopulation of GABAergic interneurons issuing distinct axonal projections. They are known to inhibit other types of interneurons as well as excitatory principal neurons and possess a disinhibitory net effect in cortical circuits. In order to elucidate their targeting specificity, the output connectivity of VIP interneurons was studied at the subcellular level in barrel cortex of interneuron-specific Cre-driver mice, using pre- and postembedding electron microscopy. Systematically sampling VIP boutons across all layers, we found a substantial proportion of the innervated subcellular structures were dendrites (80%), with somata (13%), and spines (7%) being much less targeted. In layer VI, a high proportion of axosomatic synapses was found (39%). GABA-immunopositive ratio was quantified among the targets using statistically validated thresholds: only 37% of the dendrites, 7% of the spines, and 26% of the somata showed above-threshold immunogold labeling. For the main target structure "dendrite", a higher proportion of GABAergic subcellular profiles existed in deep than in superficial layers. In conclusion, VIP interneurons innervate non-GABAergic excitatory neurons and interneurons at their subcellular domains with layer-dependent specificity. This suggests a diverse output of VIP interneurons, which predicts multiple functionality in cortical circuitry beyond disinhibition.